Speech Acts in Multimodal Governance: A Linguistic Landscape Analysis of Regulatory Signage at Prof. Ngoerah Hospital, Bali - Giri, Ni Kade Yuliani (e-Journal of Linguistics, 2025)
This study investigates regulatory signage at Prof. Dr. I.G.N.G. Ngoerah Denpasar hospital as a multimodal Linguistic Landscape (LL) that communicates institutional identity, authority, and behavioural norms in public space. LL research in Indonesia has largely focused on tourism, transportation hubs, and cultural sites, hospital environments remain underexplored despite their semiotic richness and governance function. The research aims to describe and interpret the multimodal composition of regulatory signs related to waste disposal. It also explains their communicative functions using LL, multimodality, and speech act theory. The study employs a qualitative approach based on documentation and descriptive analysis. Data were collected through field photography of signage within the hospital environment. The those were analysed using multimodal frameworks and pragmatic models. The analysis reveals three semiotic components—image, colour, and text—working cohesively to construct meaning. Institutional logo elements encode ideological values, colour palettes convey psychological reassurance and authority, while verbal constructions alternate between expressive acts (“thank you for disposing of waste properly”) and directive acts (“maintain cleanliness”). Findings indicate that signage serves as multimodal governance rather than mere instruction. Signs strategically balance visual authority and linguistic politeness to shape public behaviour. It supports theoretical claims that LL functions as discourse in place. The study concludes that hospital signage operates as a dynamic communicative system, integrating symbolic identity, persuasive emotion, and directive force to regulate conduct. These insights extend LL scholarship to healthcare contexts and demonstrate the relevance of speech act analysis in multimodal public communication.